Предмет: Алгебра,
автор: mariy02
(х-5)(х+4)=(х-5)(0.9х-0,5)
Ответы
Автор ответа:
0
(х-5)(х+4)=(х-5)(0.9х-0.5)
(х-5)(х+4)-(х-5)(0.9х-0.5)=0
(х-5)[(х+4)-(0.9х-0.5)]=0
(x-5)(x+4-0,9x+0,5)=0
(x-5)(0,1x+4,5)=0
x-5=0
x=5
0,1x+4,5=0
0,1x=-4,5
x=-4,5:0,1
x=-45
Ответ х=5 и х=-45
(х-5)(х+4)-(х-5)(0.9х-0.5)=0
(х-5)[(х+4)-(0.9х-0.5)]=0
(x-5)(x+4-0,9x+0,5)=0
(x-5)(0,1x+4,5)=0
x-5=0
x=5
0,1x+4,5=0
0,1x=-4,5
x=-4,5:0,1
x=-45
Ответ х=5 и х=-45
Похожие вопросы
Предмет: Английский язык,
автор: rubashevskiikirill
Предмет: Математика,
автор: Helloheyhi
Предмет: Алгебра,
автор: Kkiiiiiigggiii
Предмет: Алгебра,
автор: Etozhezanuda
Предмет: Математика,
автор: Аноним